Mrica Reservoir Sedimentation: Current Situation and Future Necessary Management - Puji Utomo (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2017)
Mrica Reservoir is one of many reservoirs located in Central Java that experienced a considerably high sedimentation during the last ten years. This condition has caused a rapid decrease in reservoir capacity. Various countermeasures have been introduced to reduce the rate of the reservoir sedimentation through catchment management and reservoir operation by means of flushing and/or dredging. However, the sedimentation remains intensive so that the fulfillment of water demand for electrical power generation was seriously affected. This paper presents the results of evaluation on the dynamics of the purpose of this research is to evaluate the sediment balance of the Mrica Reservoir based on two different scenarios, i.e. the existing condition and another certain type of reservoir management. The study on sediment balance was carried out by estimating the sediment inflow applying sheet erosion method in combination with the analysis of sediment rating curve. The measurement of the deposited sediment rate in the reservoir was conducted through the periodic echo sounding, whereas identification of the number of sediment that has been released from the reservoir was carried out through the observation on both flushing and dredging activities. The results show that during the last decade, the rate of the sediment inflow was approximately 5.869 MCM/year, whereas the released sediment from the reservoir was 4.097 MCM/year. In order to maintain the reservoir capacity, therefore, at least 1.772 MCM/year should be released from the reservoir by means of either flushing or dredging. Sedimentation management may prolong the reservoir’s service life to exceed the design life. Without sediment management, the lifetime of the reservoir would have finished by 2016, whereas with the proper management the lifetime may be extended to 2025.